PEMILIHAN BAHAN MATERIAL KONSTRUKSI BAHU JALAN BERDASARKAN JENIS KERUSAKAN DAN ANALISA EKONOMINYA (STUDI KASUS JALAN BATAS KOTA TAKENGON - UWAK) - Usman Usman; Sofyan M. Saleh; Yuhanis Yunus (Prodi Magister Teknik Sipil Unsyiah, 2019)
This research is located in Takengon - Uwak City boundary section. The benefit of this research is to figure out the proper type of road construction for investment based on financial feasibility with respect to Vehicle Operational Cost (VOC), Benefit Cost Ratio (BCR), Net Present Value (NPV), and Internal Rate of Return (IRR). The data used in this study was secondary data obtained from related institutions. The research method used in this research was economic indicators with two scenarios, that is; 1. Road improvement with no handling/ existing (Do Nothing), and 2. Road improvement. From the calculation results, it was obtained the price of construction and maintenance for each shoulder of the road construction, that is, the shoulder using Material Class B was IDR 5.493.388.958, the material class B shoulder with Geocel IDR. 4.946.201.289, and road construction using concrete IDR. 6.162.438.275. The saving of VOC produced was IDR. 23,006,00. The results of the economic analysis performed for the three types of construction with the Net Present Value (NVP) method resulted in Road Construction by Shoulder Using Materials Class B and Geocell is the best alternative to make an investment because it produces the largest NPV Value, that is, NPV=IDR 1,808,869,588,00. The highest BCR value is BCR = 1.49, with IRR value = 14.855%